The role and mechanism of histone lactylation in health and diseases - Xie, Yumei; Hu, Hongxia; Liu, Maoting; Zhou, Tingting; Cheng, Xi; Huang, Wei; Cao, Ling (Frontiers in Genetics, 2022)
Whether under anaerobic or aerobic conditions, glycolysis results in production of lactate. Increasing evidence suggests that lactate serves as a multifunctional signaling molecule that develops non-metabolic activities in addition to serving as a key metabolite to link glycolysis and oxidative phosphorylation. Histone posttranslational modification patterns (HPTMs) are essential epigenetic processes controlling a variety of biological activities. Proteomics based on mass spectrometry (MS) has been used to progressively reveal new HPTMs. Recent discoveries of histone lactylation modification mediated by lactate and subsequent research demonstrating its involvement in cancer, inflammation, lung fibrosis, and other conditions suggest that it plays a significant role in immune regulation and homeostasis maintenance. This review provides a brief overview of the complicated control of histone lactylation modification in both pathological and physiological conditions.